The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-2648.2000.t01-1-01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying clinical decision making: a unifying approach

Abstract: This is the first of two linked papers exploring decision making in nursing which integrate research evidence from different clinical and academic disciplines. Currently there are many decision-making theories, each with their own distinctive concepts and terminology, and there is a tendency for separate disciplines to view their own decision-making processes as unique. Identifying good nursing decisions and where improvements can be made is therefore problematic, and this can undermine clinical and organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…By identifying our use of decision-making theories we can examine how decisions are reached and learn from our experiences. Buckingham and Adams (2000) propose that there is inconsistency in the variety of theories of decision-making, suggesting a single framework to allow unified evaluation, whilst Offredy (1998) identified that the clinical problem dictated the decision model used. An alternative method of decision making is the information processing model or hypothetico-deductive reasoning.…”
Section: Decision-making Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…By identifying our use of decision-making theories we can examine how decisions are reached and learn from our experiences. Buckingham and Adams (2000) propose that there is inconsistency in the variety of theories of decision-making, suggesting a single framework to allow unified evaluation, whilst Offredy (1998) identified that the clinical problem dictated the decision model used. An alternative method of decision making is the information processing model or hypothetico-deductive reasoning.…”
Section: Decision-making Theorymentioning
confidence: 99%
“…Determining the strategic process of our decision-making will help in the justification and overall enhancement of our professional status (Buckingham and Adams, 2000). This paper describes the strategies used by nurses when assessing and determining a clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…A brief overview of clinical decision making theories was given in Buckingham & Adams (2000). These theories will now be compared to classification behaviour to draw out their similarities and differences.…”
Section: Theories Of Clinical Decision Making Interpreted As Classifimentioning
confidence: 99%
“…In the linked paper ‘Classifying clinical decision making: a unifying approach’ (Buckingham & Adams 2000), it was argued that nurses and their employers would derive important benefits from a better understanding of nurses’ decision making. These include enhanced clinical and organizational effectiveness, improved ability to work in partnership with patients, better protection against litigation, and facilitation of quality management.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the upstream oil and gas industry a few taxonomies of decision-making have been published to date [12][13][14][15][16]. Addressing similar needs in the information systems, nursing, engineering and strategic decision-making fields, these taxonomies were constructed using empirical or other observational means and are thus specific to their industry.…”
Section: Introductionmentioning
confidence: 99%